South Asia: Agricultural and rural development -- proceedings of seminars, March 2005 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
IFPRI has had a long presence in South Asia, identifying ways to eliminate the deep-seated poverty in the region, exploring the impact of the Green Revolution, and undertaking major work on subsidies, trade, markets, nutrition, adoption of agricultural technology, and other issues critical for the region. Over the last few years, IFPRI has intensified its activities in South Asia, given the persistence of poverty in the region and the new opportunities and challenges it faces. This renewed commitment is exemplified by IFPRI’s South Asia Initiative (an effort to bring together IFPRI staff and researchers and policymakers from the region in a more focused way) and by its South Asia office, opened in New Delhi this past March.